The Effect of Non-specific Response Inhibition Training on Alcohol Consumption: An Intervention - Bartsch, A.; Kothe, E.; Allom, Vanessa; Mullan, Barbara; Houben, K. (2016)
Objective: Excessive alcohol consumption increases the risk of alcohol-related disease and injury. Poor response inhibition; the inability to intentionally override a pre-potent response, has been associated with greater alcohol consumption. The aim of the present study was to clarify if non-specific response inhibition training could improve response inhibition, and reduce alcohol consumption. Method: One hundred and sixty-eight undergraduates were randomly assigned to either an inhibition or active control condition, and completed a stop-signal task once a day for four consecutive days. The inhibition condition comprised a stop-signal task with a high target density (50% stop-signals), while the active control comprised a stop-signal task with a lower target density (25% stop-signals) and the instruction to ignore the signal. Before and after the intervention, participants completed measures of response inhibition, and alcohol consumption. Alcohol consumption was measured again at one month post-training. All parts of the study were completed online. Results: Contrary to the hypotheses, participants in the inhibition condition did not have lower levels of alcohol consumption, nor improved response inhibition after the intervention, compared to participants in the active control condition. Conclusion: It is suggested that response inhibition training needs to be specific to the target behaviour in order to be effective; however, that training did not improve response inhibition itself, calls into question the efficacy of this particular training paradigm. It is recommended that future response inhibition training paradigms consider how training intensity, and the format of administration, influences behavioural outcomes.